Food security and business opportunity: lessons from surah Yusuf - Mohd Marzuki, Zunaidah (AbdulHamid AbuSulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia and Majlis Keselamatan Negara., 2022)
Lessons from the Prophetic story on food crisis can be learned through the story of the Prophet Yusuf which Allah has revealed to the Prophet Muhammad (PBUH).